Research into the influence of the media on the popularity of public catering establishments - Saduova Dara; Daria Atasheva (Progress in Science, 2024)
The study aims to analyze the impact of the media on the level of popularity of public catering establishments. Various media platforms and their influence on consumer perception and choice are analyzed, and the effectiveness of advertising strategies for enterprises in this industry is assessed. The results of the study can provide valuable insights for business and marketing in the food service industry.